Abundant geographical divergence of Clostridioides difficile infection in China: a prospective multicenter cross-sectional study - Lulu Bai; Telong Xu; Wenzhu Zhang; Yajun Jiang; Wenpeng Gu; Wei Zhao; Yang Luan; Yanfeng Xiong; Nianli Zou; Yalin Zhang; Ming Luo; Jinxing Lu; et al. (BMC Infectious Diseases)
Abstract Clostridioides difficile is the predominant pathogen in hospital-acquired infections and antibiotic-associated diarrhea. Dedicated networks and annual reports for C. difficile surveillance have been established in Europe and North America, however the extensive investigation on the prevalence of C. difficile infection (CDI) in China is limited. In this study, 1528 patients with diarrhea were recruited from seven geographically representative regions of China between July 2021 and July 2022. The positivity rate of toxigenic C. difficile using real-time fluorescence quantitative PCR test of feces was 10.2% (156/1528), and 125 (8.2%, 125/1528) strains were successfully isolated. The isolates from different geographical areas had divergent characteristics after multilocus sequence typing, toxin gene profiling, and antimicrobial susceptibility testing. No isolate from clade 2 were found, and clade 1 was still the main clade for these clinical isolates. Interestingly, clade 4, especially ST37, previously known as the characteristic type of China, showed a strong geographical divergence. Clade 3, although rare in China, has been detected in Hainan and Sichuan provinces. Most C. difficile isolates (76.8%, 96/125) were toxigenic. Clindamycin, erythromycin, and moxifloxacin were the top three antibiotics to which resistance was observed, with resistance rates of 81.3%, 63.6%, and 24.0%, respectively. Furthermore, 34 (27.2%, 34/125) multidrug-resistant (MDR) strains were identified. All the strains were sensitive to metronidazole, vancomycin, and meropenem. The genotype of C. difficile varies greatly among the different geographical regions in China, and new types are constantly emerging. Therefore, comprehensive, longitudinal, and standardized surveillance of C. difficile infections is needed in China, covering typical geographical areas.